Вплив роботи стабілізатора поперечної стійкості на безпеку руху автомобіля по нерівній дорозі - Поляков, Віктор; Шарай, Світлана; Разбойніков, Олександр (Видавництво Львівської політехніки, 2018)
The results of the research of uniform rectilinear movement of a car on a bearing surface, which has a sinusoidal road roughness, was presented. The calculations takes into account changing in the transfer function of the suspension system, as well as the work of bump stop and rebound bumper. Conducted calculations for a car Renault 15TS with anti-roll bar and without was presented.
Influence of anti-roll bar on road safety of car while driving on uneven road
Keywords: 629.113